Behavioural indicators of pain in crustacean decapods - Francesca Gherardi (Istituto Superiore di Sanità, 2009)
Whether invertebrates are able or not to experience pain is a highly controversial issue. An operative way to solve such a controversy might be to investigate their responses to potentially noxious stimuli and to collect evidence of their behavioural complexities as proxies of cognitive capacities. The principle of argument-by-analogy can be then applied to these data: the behaviour displayed by invertebrates is compared with that of "higher" animals, its similarity denoting the former's capacity to have analogous experiences. Here, the author discusses some examples, extracted from the literature on crustacean decapods, that pinpoint their nature of "sentient" animals. This review, however, also shows that research is still scanty in the field. The studies that examine the potential links between stress responses and pain experience are few, and the several papers that help elucidate cognitive abilities in decapods have been limited to a few taxa and are not specifically directed to the question of "sentience". On the contrary, also in the light of the expected revision of the current EU legislation in the matter, more scientific efforts should be expended on exploring the issue of pain experience in invertebrates.